Novel regioselective sulfamidomethylation of phenols: Synthesis characterization, biological effects, and molecular docking study - Askarova, Kamala; Mammadova, Sevgili; Farzaliyev, Vagif; Sujayev, Afsun; Sadeghian, Nastaran; Taslimi, Parham; Kilinc, Namik; Sadeghian, Nastaran; Taslimi, Parham (Elsevier, 2024)
Studied the reaction of sulfamidomethylation of phenols in the presence of a catalytic amount of hydrochloric acid (0.001 mol per 1 mol of sulfamide), which accelerates the reaction and increases the yield of the target product to 75-85 %. The study of the direction of the reaction showed that the attack of the carbocation is directed mainly towards the ortho position with respect to the hydroxyl group of phenol. Additionally, it is demonstrated that the enzymes alpha-glycosidase, aldose reductase, and alpha-amylase are blocked by novel regioselective sulfamidomethylation of phenols L(1-4). With an IC50 value of 4.41 mu M, compound L4 in this series exhibited the least inhibitory impact on aldose reductase (AR), whereas compound L1 displayed the most inhibitory effect with an IC50 value of 3.28 mu M. These chemicals also readily inhibited the enzymes alpha-amylase and alpha-glycosidase. The ability of each material to inhibit the alpha-glycosidase enzyme was tested; the IC50 values ranged from 3.53 to 9.33 mu M and the Ki values ranged from 4.25 +/- 0.43 to 11.70 +/- 0.87 mu M. Furthermore, the alpha-amylase's effective inhibition percentage (IC50) ranges from 0.27 to 1.46 mu M. The inhibition potential of novel regioselective sulfamid compounds L(1-4) on alpha-glycosidase and alpha-amylase was assessed using p-NPG and starch as the substrates, according to Tao et al. and Xiao et al. techniques. Since the results are meaningful, they may be used for drug design.
Keywords: Sulfonamides; Enzyme Inhibition; Molecular Docking; Sulfamidomethylation; Chromenes